Clays in the minerals processing value chain - Gräfe, Markus; Klauber, Craig; McFarlane, Angus J.; Robinson, David J. (Cambridge University Press, 2017)
Clays are increasingly becoming a major problem in the mining, extraction and value-adding processes for a wide range of commodity raw materials. Clays can impact negatively on virtually every unit process within the mining and minerals processing sector, having long-term environmental implications that go well beyond the lifetime of the mining operation. This book is the first to compile, explain and evaluate the effects of clays in the mineral processing value chain, from mining to minerals processing, and finally, tailings disposal. Focusing on topics from the chemistry and rheology of clays to their detection and dissolution behaviour, this book provides comprehensive coverage of the effects on processes such as settling, preg-robing, flotation and comminution. It is an excellent reference for professional mineralogists and geologists, industrial engineers, and researchers interested in clays and clay minerals